Midiatização do telejornalismo: um estudo sobre a produção de notícias a partir da inserção do telespectador como produtor de conteúdo - Padilha, Eliziete dos Santos (Universidade do Vale do Rio dos Sinos, 2017)
This research studies the constitution of the mediatization process of journalism specifically in the production of news for television. The movements between reception, production and institutions are investigated based on the use of media devices, mainly smartphones. In this articulation, we sought to understand how the media appropriation of images, in a circulation process, defines the criteria of content in television news and how the viewers are increasingly configured as co-managers of information, offering their inputs to journalists. The research shows that amateur records aim at catching the flagrant, the unusual, because they are images with greater potential to reach the media system and, thus, generate symbolic recognition to their authors. This study also shows how the discursive marks of social actors and non-media institutions intensify the language effects of television, redesign journalistic practices and generate new links between TV and society.
Keywords: Midiatização; Jornalismo; Circulação; Televisão; Mediatization; Journalism; Circulation; Television; ACCNPQ::Ciências Sociais Aplicadas::Comunicação